RAILWAY-RELATED ABBREVIATIONS IN ENGLISH: A COMPREHENSIVE OVERVIEW (Proceedings of Scientific Conference on Multidisciplinary Studies, 2024)
Railway systems rely on numerous abbreviations to streamline communication, ensure safety, and optimize operations. This study aims to provide a comprehensive overview of railway-related abbreviations in the English language. Through a systematic analysis of literature and empirical data, this research sheds light on the prevalence, usage patterns, and significance of these abbreviations in the railway industry.